The influence of internal surface treatments on tensile bond strength for two ceramic systems - Kiyan, V. H.; Saraceni, C. H. C.; Silveira, B. L.; Aranha, A. C. C.; Eduardo, C. P. (Operative Dentistry Inc, 2007)
Statement of the Problem: the ceramic composition and surface microstructure of all-ceramic restorations are important components of an effective bonding substrate. Hydrofluoric acid and sandblasting are well-known procedures for surface treatment; however, surface treatment for high alumina-containing and lithium disilicate ceramics have not been fully investigated.Purpose: This in vitro study evaluated the tensile bond strength of resin cement to two types of ceramic systems with different surface treatments.Methods and Materials: Thirty specimens of each ceramic system were made according to the manufacturer's instructions and embedded in polyester resin. Specimens of In-Ceram Alumina [1] and IPS Empress 2 [E] were distributed to three groups with differing surface treatments (n=10): sandblasting with 50 jam aluminum oxide (APA); sandblasting with 110 pm aluminum oxide modified with silica particles (ROCATEC System-RS); a combination of sandblasting with APA and 10% hydrofluoric acid etching (HA) for two minutes on In-Ceram and for 20 seconds for IPS Empress 2. After the respective surface treatments, all the specimens were silanated, and Rely-X resin cement was injected onto the ceramic surface and light polymerized. The specimens were stored in distilled water at 37 degrees C for 24 hours and thermally cycled 1,100 times (5 degrees C/55 degrees C). The tensile bond strength test was performed in a universal testing machine at a 0.5 mm/minute crosshead speed.Results: the mean bond strength values (AWa) for IPS Empress 2 were 12.01 +/- 5.93 (EAPA), 10.34 +/- 1.77 (ERS) and 14.49 +/- 3.04 (EHA). The mean bond strength values for In-Ceram Alumina were 9.87 +/- 2.40 JAPA) and 20.40 +/- 6.27 (IRS). All In-Ceram specimens treated with 10% hydrofluoric acid failed during thermal cycling.Conclusion: the Rocatec system was the most effective surface treatment for In-Ceram Alumina ceramics; whereas, the combination of aluminum oxide sandblasting and hydrofluoric acid etching for 20 seconds worked more effectively for Empress 2 ceramics.